The effect of cavity depth on accuracy of intraoral scanners in intra-coronal restorations - Yunus Emre Özden; Bengü Doğu Kaya; Çağla Akbal; Pınar Yılmaz Atalı; Zeynep Özkurt-Kayahan (BMC Oral Health)
Abstract Purpose This study aimed to evaluate the effect of cavity depth on the accuracy of intraoral scanners (IOS) in intra-coronal restorations, focusing on trueness and precision as defined by International Organization for Standardization (ISO) 5725 standards. Materials and methods Three intra-coronal cavity designs with depths of 2.5 mm (n = 10), 5 mm (n = 10), and 7.5 mm (n = 10) were fabricated using 3-Dimentional (3D) printed tooth models. Scans (n = 30) were performed using the Trios 3 intraoral scanner, and accuracy was assessed by comparing scanned models to reference models. Trueness was measured as the root mean square (RMS) deviation, and precision was calculated from the interquartile range of average absolute distances. Statistical analyses were conducted using the Kruskal-Wallis test and Mann-Whitney U test with Bonferroni correction. Results The accuracy of the IOS was significantly lower at a cavity depth of 7.5 mm compared to 5 mm and 2.5 mm (p < 0.05). RMS values were highest for the 7.5 mm depth, while the lowest precision was observed at this depth. Conclusion Cavity depth significantly affects the accuracy of IOS in intra-coronal restorations, with deeper cavities resulting in reduced accuracy. This highlights the importance of considering cavity depth when planning IOS workflows. This study shows that scanning accuracy decreases when the distance between the cavity floor and the cusp tip exceeds 5 mm. Elevating the cavity floor with direct methods may help improve scanning accuracy and enhance restoration outcomes.